An Approach to Effective Village Finance Management through the Use of Simulacra and Hyperreality - Puja Rizqy Ramadhan; Suwarno; Shella Pratiwi (International Forum of Researchers and Lecturers, 2024)
The purpose of this research is to examine Jean Baudrillard's views on simulacra and hyperreality in light of the idea of effective village governance. Primary data for this study came from interviews and observations of informants. This study employed a qualitative methodology. Data reduction, data presentation, and data gathering processes make up the study. Findings suggest that Good Village Governance might push people and communities into a hyperrealistic condition where the line between reality and perception blurs. Additionally, this arrangement makes information more susceptible to manipulation, which is something that village authorities, who are responsible for overseeing the money, should be cognizant of. It is imperative that village officials, in this age of inevitable modernity and globalization, fortify the components of professional ethics, moral culture, and spirituality in order to produce officials who are not only competent but also able to serve as positive examples to the rest of society.